The The Impact of Job Satisfaction on the Performance of Educators and Education Personnel of Pondok Pesantren Manbaul 'Ulum Duku Puntang Cirebon West Java - Wiwin; Mubarok, Endang Saefuddin; Sekarini, Ratih Ayu; Tasyriq, Muhammad Fajar; Siregar, Ahmad Munawir (International Journal of Integrative Sciences, 2024)
This research aims to make efforts to analyze, collect data and information related to internal communication, motivation, organizational commitment, work ethic, job satisfaction, and employee performance. The results of this study provide practical benefits in managing organizational organizations, especially for Pesantren Mambaul 'Ulum Duku Puntang-Cirebon This research design is descriptive and explanatory quantitative, with multivariate analysis methods. The research sample amounted to 205 people. Data collection with questionnaire instruments and analyzed with structural equation models. The results of the study (1) Internal communication has a significant effect on employee performance, but has no significant effect on job satisfaction (2) Motivation has a significant effect on employee performance, but has no significant effect on job satisfaction; (3) Organizational commitment has a significant effect on job satisfaction, but has no significant effect on employee performance;: (4) Work ethic has an insignificant effect on employee performance, but a significant effect on job satisfaction; (5) Job satisfaction has a significant effect on performance; employees and (6) The significance of the strength value of the dependent variable is evident through the calculation of the square value of multiple correlations (R2) for both job satisfaction and employee performance